The Impact of community-Based Waste Bank Programs on Environmental Awareness: Evidence from Bontang City - Fadhila Fadhila; Daryono Daryono; Cathas Teguh Prakoso (Jurnal Pemerintahan dan Politik Lokal, 2026)
This study aims to know the impact of community-based Waste Bank Program in improving the community environmental awareness in Bontang City, particularly in terms of changes in knowledge, attitudes, and environmentally responsible behavior. This study employed an associative quantitative design using a survey approach. Data were collected through a structured questionnaire administered to 100 respondents selected using stratified random sampling. The independent variable was the impact of community-based Waste Bank Program, while the dependent variable was environmental awareness. Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results indicated that the implementation of the Waste Bank Program has a positive and significant effect on community environmental awareness. The program improves public understanding of waste management, strengthens positive attitudes toward environmental protection, and promotes environmentally responsible behavior, particularly in waste sorting and reduction practices. These findings suggested that community-based waste management can serve as an effective public policy instrument in promoting sustainable environmental behavior at the local level. The novelty of this study lies in its quantitative evaluation of Waste Bank implementation in a coastal industrial city, thereby providing empirical evidence to strengthen local environmental governance and community-based waste management policies.